The effect of curcumin on rat ovarian reserve following ischemic reperfusion injury - Abbas Shahedi; Mina Malekpoor Afshar; Maryam Yadegari; Ali Reza Talebi; Abolghasem Abbasi-Sarcheshmeh; Mahmood Vakili (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2022)
Introduction: Ischemia-reperfusion injury is an important problem for ovarian torsion. It is generally caused by the damage of reactive oxygen species. Antioxidant agents such as curcumin may protect the ovaries from damage caused by oxygen free radicals. The present study was performed aimed to evaluate the effects of curcumin on ischemic-reperfusion (I / R) injury by evaluating biochemical and histopathological parameters. Methods: Thirty-six female Wistar rats (200-250g) were divided into six experimental groups: control, sham, torsion (3 hours of ischemia), torsion and detour (3 hours of ischemia and 3 hours of reperfusion) and treatment groups 1 and 2 (Ischemia was divided into 3 hours, reperfusion for 3 hours and then intraperitoneal injection of 100 mg / kg curcumin half hour before detorsion and half hours after detorsion). Malondialdehyde (MDA) test was performed by taking blood samples from rats and special kits. After ovarian resection, hematoxylin and eosin (H&E) staining was performed for histopathological evaluation of the ovary. Data were analyzed by SPSS statistical software (version 18) and one-way variance and Kruskal-Willis statistical tests. P< 0.05 was considered statistically significant. Results: The amount of malondialdehyde (MDA) showed a significant difference in the torsion and detour groups compared to other groups (P <0.001). In histopathological evaluation, the number of ovarian follicles at different stages of development showed a significant decrease in torsion and detour groups compared to control, sham and treatment groups (P <0.001), but no significant difference was observed between the treatment groups. The number of corpus luteum was significantly reduced in the treatment, torsion and detour groups compared to the control and sham groups (P <0.001). Conclusion: Curcumin probably maintains ovarian function through its antioxidant and anti-inflammatory properties following ischemic-reperfusion injury. Keywords: Curcumin, Ischemia, Ovary, Rat, Reperfusion.